Torsadogenic index for prevention of acute death - Inchauspe, Adrián Ángel (2015)
This risk management project aims to apply a global preventive and predictive measure in potential victims of acute death and heart failure. Among the main causes are identified sub-diagnosed genetic mutations; prescription, interaction, self-medication or abuse of suspected drugs due to internet prospect's consult; and a parasitic pandemia, the Chagas disease (over 100 000 000 population is potentially infected worldwide). Promoting a global extensive determination of the torsadogenic index which was successfully published in Frontiers of Pharmacology Journal, will allow to monitor general population, set security patterns to categorize silent high risk groups of serious prognosis of tachyarrhythmias. For this purpose, applications of known QT determinations are proposed, recommending Dr. Rautaharju's formula, actually improved with gender adult versions. Torsadogenic index will allow to establish an individual traceability, obtain comparative samples that are alert to possible QT enlargements. Thus, torsadogenic index results a valuable, simple and costless resource to consider in the fight against acute death and cardiac arrest. Torsadogenic index represents a global indicator capable of predicting and preventing acute death and heart failure for most relevant reasons.